Urgent Need for National Maritime Security Arrangement in Indonesia: Towards Global Maritime Fulcrum - Puspitawati, Dhiana (UI Scholars Hub, 2017)
Under President Joko Widodo’s administration, Indonesia’s archipelagic outlook has been re-asserted as the basis of Indonesia’s foreign policy, by introducing the concept of Global Maritime Fulcrum (GMF). GMF is aimed put Indonesia as a single maritime power with considerable diplomatic influence in becoming a central role in two vast maritime regions. The implementation requires the maintenance of three key areas national sovereignty, maritime security and regional stability. While the scope of maritime threats has been broaden, the establishment of maritime security should encompasses at least three key areas, namely settling unresolved maritime border with neighboring countries; combating illegal, unreported and unregulated fishing as well as other illegal exploitation of ocean resources; and combating maritime piracy and armed robbery at sea. Unfortunately those are the biggest problems Indonesia has over security and stability of Indonesia’s maritime. Such problems are mainly due to the lack of national maritime security arrangement. The existing national legal frameworks in maritime security issues are still very sectoral in nature. In addition, inconsistency between existing domestic legal framework with international legal framework, and a non-updated existing legal framework raised problems with regard to the law enforcement at sea. This paper analyses Indonesia’s current sectoral legal framework on maritime security towards the achievement of GMF. It is argued that in maintaining national sovereignty, maritime security and regional stability, single national maritime security arrangement is needed.